Wild relatives and interspecific hybrids of potato as source materials in breeding for resistance to golden nematode - N. V. Mironenko; E. V. Rogozina; A. A. Gurina; A. V. Khiutti; N. A. Chalaya; O. S. Afanasenko (Труды по прикладной ботанике, генетике и селекции)
Background. Predominant use of the H1 and Gro1-4 genes of resistance to golden nematode (PGN) in potato breeding requires widening the gene pool of resistance to this pathogen.Materials and methods. Thirty-four genotypes of wild potatoes from North and South Americas, 14 interspecific hybrids, and 10 Russian potato cultivars were studied for PGN resistance. Screening for resistance to PGN pathotype Ro1 and molecular screening for the presence of H1 and Gro1-4 gene markers were performed. Amplification products of the Gro1-4 gene marker were sequenced.Results. Only seven among the studied 34 potato genotypes (two of S. brachystotrichum (Bitt.) Rydb., four of S. lesteri Hawkes et Hjerting, and one of S. kurtzianum Bitt. et Wittm.) were susceptible to PGN, while the rest demonstrated high or medium resistance. Molecular screening for the presence of H1 and Gro1-4 gene markers allowed us to identify Gro1-4 in 13 South American genotypes of S. alandiae Cárd., S. × doddsii Corr., S. kurtzianum, S. leptophyes Bitt., and S. yungasense Hawkes. The remaining 14 genotypes may supposedly contain resistance genes non-identical to H1 or Gro1-4. Hybrids of S. tuberosum L. with medium-resistant wild accessions of S. kurtzianum, S. leptophyes, S. sparsipilum (Bitt.) Juz. et Buk., S. alandiae, and S. × doddsii inherited PGN resistance determined either by the Gro1-4 gene or genes non-identical to H1 or Gro1-4. Sequencing a fragment of the Gro1-4 gene showed that changes in the structure of this fragment in orthologous genes did not affect the feature of resistance to PGN pathotype Ro1.Conclusion. For the first time, sources of resistance to PGN were found among the North American species S. brachystotrichum (k-23201) and S. lesteri (k-24475). Among the wild South American Solanum spp., sources of resistance determined by genes different from H1 or Gro1-4 were identified. Resistant interspecific hybrids can serve as donors of the Gro1-4 resistance gene or new resistance genes.